Generating social capital between people management and dynamic change - Emanuele Testa; Silvia Ivaldi (Akademisk Kvarter)
This articlepresents an action-research experience as an emblematic expression of new ways of generating value and organizational processes. The subject is related to the management of pre-schools, in which civil society takes responsibility for micro-processes that guarantee the generation of collective value for the community and the maintenance of a connective tissue through which narratives, stories, and experiences take root. Stories become relationships, networks of trust and collaboration with widespread availability that translates civic consciousness into actions, initiatives, and projects. The article’s contribution illustrates the challenges faced and the organizational processes activated with the different stakeholders involved in the system of activities considered, through a situated and conversational research-action approach (Shotter 2007), according to a dialogic research-action perspective (Shotter 2010). The results highlight the elements of social capital generated, as well as the critical issues that emerged in the work within the socio-organizational and community contexts.